Folic acid versus 5- methyl tetrahydrofolate supplementation in pregnancy. (October 2020) - Ferrazzi, Enrico; Tiso, Giulia; Di Martino, Daniela
Highlights: Only traces of Folic Acid are present in raw non-supplemented foods. Vitamin B9 is synthesized from Folic Acid only after a series of molecular reactions in liver. Vitamin B9, 5-MTHF, is a methyl donor in essential epigenetic processes of embryogenesis. Vitamin B9 regulates homocysteine levels and has a key role in the synthesis of DNA and RNA. In women at risk of reduced hepatic activation of Folic Acid, Vitamin B9 could be directly supplemented. Abstract: Folate (vitamin B9) is widely accepted to protect against fetal neural tube defects. The main sources of dietary folate are folic acid-fortified foods and folic acid-containing dietary supplements. However, folic acid is inactive in the human body and must be converted by the liver into the active molecule 5-methyltetrahydrofolate (5-MTHF). 5-MTHF functions as a methyl donor in many metabolic reactions, including the conversion of homocysteine into methionine, the biosynthesis of glycine from serine, and the biosynthesis of DNA precursor molecules. Therefore, folate is fundamental for growth, especially in the embryonic and fetal stages. Prescription of folic acid to women in the preconception period and during pregnancy is a consolidated practice. However, it can pose health risks in certain conditions, such as megaloblastic anemia, where it will conceal megaloblastic anemia due to vitamin B12 deficiency and in cases of reduced hepatic transformation of folic acid (e.g. due to genetic variants or during some pharmacotherapies). Some of these risks can be avoided by supplementation with 5-MTHF rather than folic acid. Because 5-MTHF does not require activation, it is immediately available to mother and fetus and does not accumulate in blood like folic acid does in cases of reduced hepatic transformation. This paper reviews the advantages and disadvantages of folate supplementation with folic acid versus 5-MTHF, with a focus on maternal and fetal health.